External Debt, Public Investment and Economic Growth in Cameroon - Ngangnchi, Forbe Hodu; Joefendeh, Roland (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
This study investigates the extent to which external debt and public investment contributes to economic growth in Cameroon - emphasising on how public investment modulates the effect of external debt on economic growth. Time series data spanning the period 1980-2018 obtained from the World Bank’s world development indicators are used, together with the Dynamic Ordinary Least Squares (OLS) approach to ascertain the nature of the long-run relationship between external debt, public investment and economic growth. Consistent with the debt-overhang and crowding-out literature, the study reveals a negative significant influence of external debt on economic growth in Cameroon. Results also reveal that there is a positive and significant direct effect of public investment on economic growth in the long run. Further results indicate that public investment and external debt positively and significantly engender economic growth. This is evidence that public investment is modulating the effect of external debt on economic growth in Cameroon. These findings suggest the need for developing country governments to create an enabling environment for private sector development, while accompanying external debt resources with domestic revenue mobilization by broadening the tax base - taxes on landed property being potential candidates